Report on some Plesionika Bate, 1888 and first record of Stylopandalus Coutiére, 1905 (Caridea, Pandalidae) from Brazilian waters - Cardoso, Irene (Zootaxa, 2009)
The Brazilian expeditions REVIZEE Central Fishery and Campos Basin Deep Sea Environmental Project collected samples from the southwestern Atlantic, between depths from 200 to 2200m. These expeditions sampled three Plesionika Bate, 1888 species: Plesionika edwardsii (Brandt, 1851), P. ensis (A. Milne Edwards, 1881) and P. miles (A. Milne Edwards, 1883). Besides that, one species of Stylopandalus Coutiére, 1905, a genus never recorded on Brazilian coast before, was collected. These four pandalids were redescribed and figured.